A Computational Implementation of Morphological Analysis and Generation of Verbs in Myanmar Language - Thu , Kaung Myat; Devi , H. Mamata; Singh , Th. Rupachandra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The field of morphological analysis and generation focuses on the study of word production, the recognition of grammatical components within words, and the creation of words that adhere to morphotactic standards. According to various research reports, finite-state techniques are fast, effective, and efficient in interpreting human language morphologies into the computational system. FOMA: a more elaborate version of Xerox’s finite state toolset can be used to implement the finite state morphology. Using FOMA toolset and other programming languages, we have already created the MM-Morph tool: a computational linguistic tool for morphological analyzer and generator for Myanmar nouns. In this paper, we describe the linguistic phenomena of the morphology of verbs and the techniques used in the system’s development process to integrate it into the existing MM-Morph tool. MM-Morph has been developed as a part of the research "Morphological Analysis and Generation for Myanmar Language using Finite State Techniques." We share the experimental evaluations conducted to assess this system’s performance. Evaluation results show that the MAG system of Myanmar verbs can identify more than (78%) of the verbs in the language.